Pemodelan Kapabilitas Organisasi terhadap Kinerja Ditinjau dari Faktor Kepemimpinan Budaya Organisasi-Perilaku Politik dalam Organisasi SKpKPKSNdKPKSWdKPKSS - Yuni Ros Bangun, Sjafri Mangkuprawira, Asep Saefuddin, Setiadi Djohar (ITB, 2010)
Organizational Capability is considered to be one of the most important issues in strategic management and human capital literature. Organizational Capbility can be understood as the all elements that work efficiently and effectively to help organization create its strategy that fits to its industry level of turbulence and to achieve company performance. Previous research confirmed the identification of nin (9) elements as organizational capabilitu. These are speed innovation, customer connectivity, seeks related change, strategic responsiveness, internationalwroking environment, ready to strategic alliances, Organizational Performance. Research shows the connerction between the three variables- Leadership- Oganizational Culture and Political Behavior in creating Organizational Capability and its impact to Organizational performance. Structural Equation modeling shows that Leadership and Organizational Culture do not have direct relationship with Organizational Performance, however both have positive relationship by Organizational Capability . Organizational Performance was directly influenced positively by Organizational Capability and negatively impacted y Organizational Politics. Leadership positively impact Organizational Capability and Organizational Culture, However Leadership negatively impact Organizational Politics